(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Enhancing employee job performance is crucial for organizational profitability and competitiveness. This study explores the relationship between innovative work behavior (IWB) and employee job performance (EJP) in major food and beverage companies in Nigeria’s Niger Delta Region. A sample of 210 randomly selected employees from seven purposively drawn major food and beverage companies in the Niger Delta Region of Nigeria were surveyed using a cross-sectional methodology and collected data analyzed via Spearman Rank Correlation Coefficient in SPSS. IWB was measured through idea generation, idea sharing, and idea realization; while job performance was measured with task and contextual performance. The results of data analysis revealed a positive and significant correlation between IWB and EJP, highlighting the importance of idea generation, idea sharing, and idea realization in improving task and contextual performance in the food and beverage industry in the Niger Delta Region of Nigeria. Building on these findings and conclusion above, recommendations for managers include fostering effective communication, openness, risk-taking, brainstorming, team building, and a low tolerance for failure. Implementing these strategies is expected to stimulate innovation among employees, leading to better job performance. The study also discusses theoretical and practical implications for enhancing employees’ job performance in the Nigerian workplace. Overall, it emphasizes the vital role of innovative work behavior in improving employee performance within the food and beverage industry in the Niger Delta Region of Nigeria.